41.7k views
1 vote
Answer for this problem please

Answer for this problem please-example-1

2 Answers

1 vote
1) first answer is -9 second answer is 3
Answer for this problem please-example-1
User Jeff Bootsholz
by
4.6k points
6 votes

Answer:

f(2) = -9, and f(-2) = 19

Explanation:

Just plug it in.

If
f(x) =2x^(2) -3x+5, and you have f(2), and f(- 2), you can do,
f(2) = -2(2^(2) )-3(2)+5, and
f(-2)=-2(-2^(2) )-3(-2)+5.

Once you do all the math, you get f(2) = -9, and f(-2) = 19.

User Taketwo
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.